SEVERE HYPOTHYROIDISM-INDUCED RHABDOMYOLYSIS IN THE ABSENCE OF A TRIGGERING FACTOR - Azmi, Mohamed Haris Bin Mohamed; Warman, Nur ‘Aini Eddy; Awang, Mohd Hazrriq; Zainordin, Nor Aisyah; Mohamad, Aimi Fadilah; Mohamed, Fatimah Zaherah; Ghani, Rohana Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Thyroid disorders are among the most common endocrine diseases globally, with hypothyroidism affecting approximately 3.4% of the Malaysian population. Muscle-related symptoms, such as fatigue, cramps, and myalgia are frequently observed in hypothyroidism and usually present with mild to moderate elevations of the muscle enzymes. However, rhabdomyolysis due to hypothyroidism, particularly in the absence of other apparent causes, is rare and is more frequently associated with Hashimoto's thyroiditis. The exact mechanism remains unclear, but it is hypothesized that hypothyroidism disrupts muscle metabolism, leading to prolonged oxidative damage and subsequently rhabdomyolysis. CASE We report a case of a 32-year-old male with no prior medical history who presented with one month of weight gain and lethargy, associated with facial puffiness for 2 weeks. He denied systemic symptoms, strenuous activity, trauma, alcohol use, or recent medications. No family history of thyroid or autoimmune disease was noted. Examination showed mild facial puffiness, no muscle weakness, and normal reflexes. Laboratory investigations revealed elevated creatinine kinase (CK) levels of 2,527 U/L (55-170), aspartate transaminase (AST) of 130.3 U/L (8-33), alanine transaminase (ALT) of 118.1 U/L (7-56) and acute kidney injury with urea 7.3 mmol/L (7-12), creatinine 182 µmol/L, and eGFR 37.6 mL/min. Thyroid function tests confirmed severe hypothyroidism with free T4 7.60 pmol/L (NR: 7.86-14.41), and TSH >49.40 mIU/L (NR: 0.38-5.33) with positive thyroid peroxidase antibody, confirming Hashimoto’s thyroiditis. No other causes for rhabdomyolysis were identified and autoimmune hepatitis screening was negative. The patient was managed with aggressive intravenous hydration and levothyroxine replacement therapy, resulting in clinical and biochemical resolution. CONCLUSION This case underscores the importance of considering hypothyroidism in the differential diagnosis of unexplained rhabdomyolysis, especially in the absence of conventional triggers. Prompt recognition and early treatment are essential in preventing complications and ensuring optimal patient outcome.